2006
DOI: 10.1101/gad.1380906
|View full text |Cite
|
Sign up to set email alerts
|

Dual degradation signals control Gli protein stability and tumor formation

Abstract: Regulated protein destruction controls many key cellular processes with aberrant regulation increasingly found during carcinogenesis. Gli proteins mediate the transcriptional effects of the Sonic hedgehog pathway, which is implicated in up to 25% of human tumors. Here we show that Gli is rapidly destroyed by the proteasome and that mouse basal cell carcinoma induction correlates with Gli protein accumulation. We identify two independent destruction signals in Gli1, D N and D C , and show that removal of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
180
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(188 citation statements)
references
References 34 publications
(44 reference statements)
6
180
0
2
Order By: Relevance
“…CLEG2-expressing mice may develop pancreatic tumors because this dominant active Gli2 allele is downstream or resistant to key posttranslational regulators of canonical Hh signaling. Posttranslational regulators downstream of Smo have been shown previously to be key determinants in the temporal and spatial control of Hh target-gene expression in tumors (32). In another study, mutations in the GLI transcription factors were identified in human PDA tumor epithelium (33).…”
Section: Discussionmentioning
confidence: 94%
“…CLEG2-expressing mice may develop pancreatic tumors because this dominant active Gli2 allele is downstream or resistant to key posttranslational regulators of canonical Hh signaling. Posttranslational regulators downstream of Smo have been shown previously to be key determinants in the temporal and spatial control of Hh target-gene expression in tumors (32). In another study, mutations in the GLI transcription factors were identified in human PDA tumor epithelium (33).…”
Section: Discussionmentioning
confidence: 94%
“…For example, protein kinase A is shown to retain Gli1 proteins in the cytoplasm (through a PKA site in the nuclear localization signal peptide) whereas active Ras signaling promotes Gli nuclear localization (Stecca et al, 2007). Second, ubiquitination and protein degradation of Gli molecules is also regulated by several distinct mechanisms, including b-TRCP-, cul3/BTBand numb/Itch-mediated Gli ubiquitination (Di Marcotullio et al, 2006;Huntzicker et al, 2006;Jiang, 2006;Pan et al, 2006;Wang and Li, 2006). In addition to protein degradation, Gli3 and (Gli2 to a less extent) can be processed into transcriptional repressors, which may be mediated by the b-TRCP E3 ligase (Wang and Li, 2006).…”
Section: Signal Transduction Of the Hedgehog Pathwaymentioning
confidence: 99%
“…These findings serve as a precedent for deregulation of GLI1 in the absence of aberrancy of HH or PATCHED. More recently, GLI1 protein stability has been shown to be another HHindependent pathway deregulation (Di Marcotullio et al, 2006;Huntzicker et al, 2006). Furthermore, MEK kinase deregulation has been shown to affect GLI1 protein stability and deregulation of this pathway (Lauth et al, 2007).…”
Section: Ews/fli1 Deregulates Gli1mentioning
confidence: 99%
“…It is also conceivable that EWS/FLI1 might target GLI1 directly for transcriptional activation. However, transcriptional activation alone might not be sufficient to activate this pathway in NIH3T3 due to a very rapid clearance of GLI1 that has been reported (Huntzicker et al, 2006). Experiments to address possible indirect effects such as alterations in protein stability are currently underway.…”
Section: Ews/fli1 Deregulates Gli1mentioning
confidence: 99%